Identification of the antibacterial efficacy of ethanolic extracts and oils of some medicinal plants against the growth of Escherichia coli invitro - Al-Hussaini, Jinan abdul-Amir Sabeeh (Journal of Kerbala for Agricultural Sciences, 2017)
The present study had thrown the light on the in vitro antimicrobial potential of the ethanolic extract of four local medicinal plants; Terminalia chebula, Lawsonia inermis , Origanum vulgare, Thymus vulgaris, and essential oils of five types of medicinal plants; Elettaria cardamomum, Eugenia caryophyllus, Trigonella foenum-graecum, Linum usitatissimum, Brassica nigra against the growth of pathogenic Escherichia coli (E. coli). The antibacterial activity was carried out by using agar well diffusion technique in Mueller-Hinton agar. The results were obtained by measured the zone of inhibition (mm) around the well that could be exhibited by each plant extract and oil following incubation of bacterial plates and expressed as mean±Standard error (SE). Ethanolic extract of Terminalia chebula was possessed the strongest antibacterial effect among the tested plant extracts, followed by Origanum vulgare and Lawsonia inermis extracts. Escherichia coli was not affected by Thymus vulgaris extract. On the other hand, Escherichia coli was variably susceptible to tow of the used essential plant oils; Elettaria cardamomum and Eugenia caryophyllus, whereas the other three plant oils were not active any more.